PERAN KEDOKTERAN REHABILITASI PADA PASIEN DENGAN PERAWATAN PALIATIF - SILAKARMA, DEDI; SUMINAR, THERESIA ELISABETH LINTANG (HEALTHY : Jurnal Inovasi Riset Ilmu Kesehatan, 2023)
Rehabilitation medicine is a multidisciplinary field aimed at enhancing patients' quality of life by improving their function. Patients receiving palliative care often experience symptoms such as fatigue, decreased functional independence, mood disturbances, pain, and breathlessness. Many rehabilitation interventions can ameliorate these symptoms. The aim of this research is to evaluate the scope and effectiveness of rehabilitation interventions and exercise programs that can enhance the quality of life and alleviate existing symptoms in palliative care patients. The research method involves a literature review on the topic and cancer rehabilitation techniques specifically applied to patients with limited life expectancy. The impact of exercises and other rehabilitation interventions on the common symptoms and disabilities experienced by this patient population is analyzed. Current available literature supports the use of exercise programs and rehabilitation interventions to improve fatigue, mood, functional independence, breathlessness, and pain. Rehabilitation practitioners and palliative care providers share common goals in their approach to patients and complement each other. Palliative care providers should consider referrals to physiotherapy (physical medicine and rehabilitation) to help optimize patients' quality of life. ABSTRAKKedokteran rehabilitasi merupakan bidang multidisiplin yang bertujuan meningkatkan kualitas hidup pasien dengan meningkatkan fungsi. Pasien dengan perawatan paliatif sering mengalami gejala seperti kelelahan, penurunan kemandirian fungsional, gangguan mood, nyeri, dan sesak napas. Banyak intervensi rehabilitasi dapat memperbaiki gejala ini. Tujuan penelitian ini untuk mengevaluasi ruang lingkup dan efektivitas intervensi rehabilitasi dan program latihan yang dapat meningkatkan kualitas hidup dan memperbaiki gejala yang ada pada pasien paliatif. Metode penelitian ini dengan Tinjauan literatur tentang topik dan teknik rehabilitasi kanker yang secara khusus diterapkan pada pasien dengan waktu hidup yang terbatas. Latihan dan intervensi rehabilitasi lainnya dianalisis pengaruhnya terhadap gejala umum dan kecacatan yang dialami oleh populasi pasien ini. Literatur yang tersedia saat ini mendukung penggunaan program latihan dan intervensi rehabilitasi untuk memperbaiki kelelahan, mood, kemandirian fungsional, sesak napas, dan nyeri. Praktisi Rehabilitasi dan perawatan paliatif memiliki tujuan yang sama dalam pendekatan terhadap pasien dan saling melengkapi satu sama lain. Penyedia perawatan paliatif harus mempertimbangkan rujukan ke fisioterapi (kedokteran fisik dan rehabilitasi) untuk membantu mengoptimalkan kualitas hidup pasien.